Autoimmune Chronic Active Hepatitis (Lupoid Hepatitis) and Primary Sclerosing Cholangitis in Two Young Adult Females - Gerald Y. Minuk; Lloyd R. Sutherland; S. Chris Pappas; James K. Kelly; Sue E. Martin (Canadian Journal of Gastroenterology)
Autoimmune chronic active hepatitis (CAH) and primary sclerosing cholangitis (PSC) arc chronic diseases of the hepatobiliary system that have many clinical, immunologic and genetic features in common. Despite these similarities, there are few reports of the two diseases coexisting. Two young women with clinical, biochemical, serologic, radiologic and histologic findings compatible with both autoimmune CAH and PSC are described. The observation that there may be a striking overlap in the features of these two diseases and recent improvements in diagnostic imaging of the biliary tract suggest that the association of these two diseases in the same individual may be more common than is presently appreciated.